Tissue-specific evaluation of suitable reference genes for RT-qPCR in the pond snail, Lymnaea stagnalis - Young, Alexander P. (PeerJ, 2019)
Reverse transcription quantitative PCR (RT-qPCR) is a robust technique for the quantification and comparison of gene expression. To obtain reliable results with this method, one or more reference genes must be employed to normalize expression measurements among treatments or tissue samples. Candidate reference genes must be validated to ensure that they are stable prior to use in qPCR experiments. The pond snail (Lymnaea stagnalis) is a common research organism, particularly in the areas of learning and memory, and is an emerging model for the study of biological asymmetry, biomineralization, and evolution and development. However, no systematic assessment of qPCR reference genes has been performed in this animal. Therefore, the aim of our research was to identify stable reference genes to normalize gene expression data from several commonly studied tissues in L. stagnalis as well as across the entire body. We evaluated a panel of seven reference genes across six different tissues in L. stagnalis with RT-qPCR. The genes included: elongation factor 1-alpha, glyceraldehyde-3-phosphate dehydrogenase, beta-actin, beta-tubulin, ubiquitin, prenylated rab acceptor protein 1, and a voltage gated potassium channel. These genes exhibited a wide range of expression levels among tissues. The tissue-specific stability of each of the genes was consistent when measured by the standard stability assessment algorithms: geNorm, NormFinder, BestKeeper, and RefFinder. Our data indicate that the most stable reference genes vary among the tissues that we examined (central nervous system, tentacles, lips, penis, foot, mantle). Our results were generally congruent with those obtained from similar studies in other molluscs. Given that a minimum of two reference genes are recommended for data normalization, we provide suggestions for strong pairs of reference genes for single- and multi-tissue analyses of RT-qPCR data in L. stagnalis.